Proxy-based 300-year High Arctic climate warming record from Svalbard. (20th August 2019) - Luoto, Tomi P.; Ojala, Antti E. K.; Zajaczkowski, Marek
Abstract: We used fossil Chironomidae assemblages and the transfer function approach to reconstruct summer air temperatures over the past 300 years from a High Arctic lake in Hornsund, Svalbard. Our aims were to compare reconstructed summer temperatures with observed (last 100 years) seasonal temperatures, to determine a potential climate warming break point in the temperature series and to assess the significance and rate of the climate warming trend at the study site. The reconstructed temperatures were consistent with a previous proxy record from Svalbard and showed good correlation with the meteorological observations from Bjørnøya and Longyearbyen. From the current palaeoclimate record, we found a significant climate warming threshold in the 1930s, after which the temperatures rapidly increased. We also found that the climate warming trend was strong and statistically significant. Compared with the reconstructed Little Ice Age temperatures in late eighteenth century cooling culmination, the present day summer temperatures are >4°C higher and the temperature increase since the 1930s has been 0.5°C per decade. These results highlight the exceptionally rapid recent warming of southern Svalbard and add invaluable information on the seasonality of High Arctic climate change and Arctic amplification.